The Predatory Pricing Practice: The Challenges of Business Competition Law on Ride-Hailing Tariff’s War - Marwah Marwah (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2022)
The predatory pricing is inherently a dynamic strategy typically taking place in a single market, whereby a firm incurs a sacrifice in the short run to exclude competitors, in order to acquire a dominant position. In order to establish fair business growth and ensure equal business opportunities, a healthy environment for the business competition is highly needed. Since 2014, the market share of the ride-hailing sector in Indonesia has been dominated by three providers, namely Grab, Gojek, and Maxim. The three companies provide subsidies and discounts on services-price so that users' rates are cheaper than conventional taxis. This certainly has led to unfair competition and is very detrimental to conventional taxi. This research is normative juridical research that uses a statutory approach and a conceptual approach to analyze the alleged predatory pricing practices in the ride-hailing industry in Indonesia from the perspective of business competition law. The results show that the imposition of unfair prices can be seen from prices gap shown in the application with prices imposition, which should be based on travel distance in order to acquire a dominant position allowing it to recoup its losses and earn supracompetitive profits in the long run. This pattern of sacrifice-then-recoupment is found in the case law as well.